2017
DOI: 10.5455/msm.2017.29.277-279
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Stroke Risk Factors in Developing Country: the Case Study of Bosnia-Herzegovina

Abstract: Introduction:The burden of stroke has been increasing worldwide, especially in developing countries. Very few data regarding epidemiology of stroke are available in Bosnia and Herzegovina (BH).Patients and methods:We undertook a retrospective hospital-based study in all hospitals existing in five cantons and one district of BH. The patients were recruited between January 1st, 2014, and December 31st, 2014, and only first-ever-in-lifetime strokes (FES) were included for evaluation.Results:A FES was diagnosed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
3
17
2
1
Order By: Relevance
“…Though hypertension is the main reported modifiable risk factor of stroke among the included primary studies, the pooled proportion of hypertension among stroke patients found in the current study is lower than the previous studies conducted in Burkina Faso [ 59 ], Iran [ 61 ], China [ 58 ], Bosnia-Herzegovina [ 69 ], Nigeria [ 70 ], and Bangladesh [ 71 ]. The possible explanation for this variation might be due to the lack of diagnostic modalities and proficiency, level of income, hypertension awareness, treatment, and control [ 72 ].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Though hypertension is the main reported modifiable risk factor of stroke among the included primary studies, the pooled proportion of hypertension among stroke patients found in the current study is lower than the previous studies conducted in Burkina Faso [ 59 ], Iran [ 61 ], China [ 58 ], Bosnia-Herzegovina [ 69 ], Nigeria [ 70 ], and Bangladesh [ 71 ]. The possible explanation for this variation might be due to the lack of diagnostic modalities and proficiency, level of income, hypertension awareness, treatment, and control [ 72 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Our review is comparable with a previous study conducted in Nigeria [ 70 ]. However, this estimated proportion of dyslipidemia among stroke patients is lower than a study conducted in Bosnia-Herzegovina [ 69 ], and China [ 58 ].…”
Section: Discussionmentioning
confidence: 64%
“…Second, the score was developed in Korean stroke patients; therefore, evaluation of its reliability in other populations is needed. In addition, the generalization of this score could be limited in low-and middleincome developing countries, because of their lack of acute stroke management systems, combined with inadequate rehabilitation services, and a lack of preventive measures in stroke patients [42][43][44]. Third, participating centers in the CRCS registry were large centers; therefore, there could be limitations related to generalization to community hospitals and small centers.…”
Section: Discussionmentioning
confidence: 99%
“…Svake dvije sekunde neko u svijetu doživi moždani udar, a svakih šest sekundi neko od njega umre. MU pogađa 33 miliona ljudi svake godine u svijetu, a jedna trećina MU se dešava u zemljama u razvoju (2). Međunarodne epidemiološke studije pokazuju da stopa raste eksponencijalno s godinama, od 0,3‰ u trećoj dekadi života, do 30‰ u osamdesetim i devedesetim godinama života, što predstavlja prosjek od 1-2‰.…”
Section: Uvodunclassified